"The Walls Are So Silent": Spaces of Confinement and Gendered Meanings of Incarceration in South African Commemorative Art. Issue 2 (2nd September 2018) - Miller, Kim
Abstract: This paper explores artistic and activist work that has arisen in response to episodes of violence committed by the apartheid state against anti-apartheid activists. More specifically, it considers representations of suffering in South Africa's public sphere through a comparison of two post-apartheid commemorative spaces: the Johannesburg Central Police Station (formerly John Vorster Square) and a memorial by artist Kagiso Pat Mautloa that is positioned there, and the Johannesburg Women's Jail at constitution Hill. Mautloa's memorial is part of the important Sunday Times Heritage Project, and it commemorates the torture and imprisonment of political detainees. The transformation of the Women's Jail into an activist and artistic space was curated by Churchill Madikida, Lauren Segal and Clive van den Berg. Through an analysis of these two spaces, I consider some of the tensions that arise in representing trauma and suffering in the public sphere and issues that arise from such tensions. How do artistic commemorations of trauma put viewers in the position of bearing witness to and upholding the memory of traumatic pasts? What is the most effective, or respectful, way to memorialise suffering? To what extent can visual culture help promote healing, recovery, and social change?